The discovery of quinoline-3-carboxamides as hematopoietic prostaglandin D synthase (H-PGDS) inhibitors. Issue 8 (15th April 2019) - Deaton, David N.; Do, Young; Holt, Jason; Jeune, Michael R.; Kramer, H. Fritz; Larkin, Andrew L.; Orband-Miller, Lisa A.; Peckham, Gregory E.; Poole, Chuck; Price, Daniel J.; Schaller, Lee T.; Shen, Ying; et al.
Graphical abstract: Abstract: With the goal of discovering more selective anti-inflammatory drugs, than COX inhibitors, to attenuate prostaglandin signaling, a fragment-based screen of hematopoietic prostaglandin D synthase was performed. The 76 crystallographic hits were sorted into similar groups, with the 3-cyano-quinoline1a (FP IC50  = 220, 000 nM, LE = 0.43) being a potent member of the 6, 6-fused heterocyclic cluster. Employing SAR insights gained from structural comparisons of other H-PGDS fragment binding mode clusters, the initial hit1a was converted into the 70-fold more potent quinoline1d (IC50  = 3, 100 nM, LE = 0.49). A systematic substitution of the amine moiety of1d, utilizing structural information and array chemistry, with modifications to improve inhibitor stability, resulted in the identification of the 300-fold more active H-PGDS inhibitor tool compound1bv (IC50  = 9.9 nM, LE = 0.42). This selective inhibitor exhibited good murine pharmacokinetics, dose-dependently attenuated PGD2 production in a mast cell degranulation assay and should be suitable to further explore H-PGDS biology.